Zakat information technology system design, zakat culture, and zakat performance – conceptual model - Elsayed, Ebtehal Atta; Yuserrie, Zainuddin (Science & Engineering Research Support Society, 2020)
Zakat is an important mechanism for the development of countries. Zakat is one of the most important aspects in Islamic Economic System. social security and harmony economic independence of the Muslim community. As well as, to strengthen important financial resource for the Islamic state. This paper seeks to investigate the impact of Zakat Information System technology (ZIST) on Zakat performance (ZP) moderating by Zakat Culture (ZC) and utilized by the application of the resource-based view (RBV) theory framework. That approach has tried to build a conceptual model to assist and explain how Zakat Information System technology (ZIST) has effects on Zakat performance (ZP). Zakat Information System technology (ZIST) defined as a way tasks perform zakat collection and distribution, includes hardware, such as machines and tools, materials, people, software and knowledge. This paper aims to reveal the influence of using new rules of Zakat Information System technology (ZIST) to improve Zakat performance (ZP) in Zakat Institutions in Malaysia. The findings of this paper add a new concept to the existing literature on Zakat Information System (ZIS). and suggests that improving Zakat Information System technology (ZIST) will improve Zakat performance (ZP) in Zakat Institutions in Malaysia.